Pengaruh Kualitas Kehidupan Kerja dan Kecerdasan Emosional terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Mediasi - Indra Gunadi; Wawan Prahiawan; Ali Imron (LP2M Universitas Ibrahimy, 2025)
This study aims to examine the influence of work life quality and emotional intelligence on employee performance mediated by job satisfaction at PT. Cilegon Karya Nusa. This study uses a quantitative approach with census sampling techniques involving 100 employees. Data were collected through questionnaires and analyzed using SmartPLS 4.0 software. External and internal models were applied to assess validity, reliability, and hypothesis testing. The results of the study indicate that Quality of Work Life has a positive and significant effect on Employee Performance, with a t-statistic value greater than the t-table value, namely 4.133 > 1.96, with a p-value of 0.00 < 0.05. Emotional Intelligence has a positive and significant impact on Employee Performance with a t-statistic value greater than the t-table value of 4.556 > 1.96 for a p-value of 0.000 < 0.05. Job Satisfaction has a positive and significant impact on Employee Performance with a t-statistic value greater than the t-table value of 2.335 > 1.96. 1.96 through p-value 0.039 < 0.05, Work Life Quality on Employee Performance is mediated by Job Satisfaction positively and significantly with a t-statistic value greater than the t-table value of 2.006 > 1.96 followed by a p-value of 0.046 < 0.05, while indicating that satisfaction cannot mediate emotional intelligence to performance, as shown by the original sample value of 0.057. Thus, the t-statistic is less than the t-table value of 1.635, less than 1.96, followed by a p-value of 0.051 > 0.05.